The opportunity to develop strategic spatial planning with the impulse of integrated territorial investments in Croatia - Katurić, Ivana; Simov, Sven (European Spatial Research and Policy, 2021)
Regional development and spatial planning in Croatia are organised as parallel planning systems regulated by different legislations and coordinated by two ministries, the development of which has been strongly influenced by the European Union (EU). In the last two decades, the intensive development of strategic documentation on a local, regional, and national level regarding diverse territorial governance aspects has had extensive analytical scope but little potential for implementation due to the overlapping of responsibilities and disconnected budget and implementation instruments. The Integrated Territorial Investments (ITI) mechanism of implementation contributed to the understanding of multifaceted territorial governance beyond strategic document drafting. This paper analyses the first phase of ITI implementation in Croatia, i.e. the processes which unified functional urban areas, creating the possibility to develop joint management structures and strategies, integrated projects, and common participative planning models.